“You Play Like That Because You’re a Girl!” A Phenomenological Analysis of the Female Gaming Experience - Gohu, Katherine Lauren (Archīum Ateneo, 2020)
As technology advanced, it created a new environment known as the online environment which now serves as another avenue for identity development. The online environment offers different “worlds” where people can meet other people and interact with them through different features that are found online. One of the most prominent online environments being online video games especially games known as the Multiplayer Online Battle Arena (MOBA) genre of games. MOBA games is a genre of online games that demands social interaction and camaraderie in order to succeed in beating the game. Despite the freedom the game offers, gender appears to play a significant role that decides how players must treat another player. I fleshed out the experiences of Female MOBA gamers vis a vis their identity development. Female MOBA Gamers find themselves subjected to experiences that are exclusive to their gender from their entry and using their female gender as part of their online identity and their experience in navigating through online sexualized and sexist behavior. Female MOBA Gamers, in the MOBA environment, describe how their gender changes the nature of their interaction with the other players in the online environment.